Light-induced processes in optically-tweezed aerosol droplets - Knox, Kerry J. (Springer, 2011)
Aerosols play a critical role in a broad range of scientific disciplines, such as atmospheric chemistry and physics, combustion science, drug delivery and human health. This thesis explores the fundamentals of a new technique for capturing single or multiple particles using light, and for characterising these particles by Raman or fluorescence spectroscopy. The outcome of this research represents a significant development in optical manipulation techniques, specifically in aerosol optical tweezing. It is demonstrated that this technique can be applied to studies of the mass accommodation of gas-phase water molecules adsorbing onto a water surface. Not only is this a fundamental process of interest to physical chemists, but it is a highly important area for understanding the roles of aerosol particles in the atmosphere and their ability to become cloud droplets. This new strategy for investigating aerosol dynamics promises to be fundamental in helping us understand the indirect effect of aerosols on the climate.